Copy of 'Self-Determinator: an organ of Irish opinion', volume 1, number 4, May 1921 - Irish Self-Determination League of Great Britain (1921)
Includes reports for Irish Self-Determination League of Great Britain districts.
Keywords: Barry, Kevin, -- 1902-1920; Lloyd George, David, -- 1863-1945; Sinn Féin; Ireland -- History -- 1910-1921; Ireland -- Politics and government -- 1910-1921